A phenylalanine at the extracellular side of Kir1.1 facilitates potassium permeation - Henry Sackin; Mikheil Nanazashvili (Taylor & Francis Group, 2024)
ABSTRACTThe Kir1.1 (ROMK) family of weak inward rectifiers controls K secretion in the renal CCT and K recycling in the renal TALH. A single point mutant of the inward rectifier, F127V-Kir1.1b was used to investigate the K transition between the selectivity filter and the outer mouth of the channel. We hypothesize that normally an aromatic Phe at the external entryway of Kir1.1b facilitates outward K secretion. We tested this by replacing F127-Kir1.1b with a small aliphatic Val. Results indicate that removal of the Phe at 127 suppresses outward currents that normally contribute to K secretion. Results with the F127V mutant could be explained by increased polyamine block and/or a decrease in the avidity of Kir1.1 for K ions near the outer mouth of the channel. The latter is supported by F127V-Kir1.1b having a lower affinity (Km = 33 mM) for K than wild-type Kir1.1b (Km = 7 mM) during external K elevation. Conversely, chelation of K with 18-Crown-6 ether reduced K conductance faster in F127V (half-time = 6s) than in wt-Kir1.1b (half-time = 120s), implying that F127V is less hospitable to external K. In other experiments, positive membrane potentials gated the F127V mutant channel closed at physiological levels of external Ca, possibly by electrostatically depleting K adjacent to the membrane, suggesting that the Phe residue is critical for outward K secretion at physiological Ca. We speculate that the avidity of wt-Kir1.1b for external K could result from a cation-Pi interaction between K and the aromatic F127.